Al-Amtsāl al-Muṣarraḥatu fi al-Suwari al-Makkiyati wa Tarjamatu Maʿāniha fi al-Luġati al-Indunisiyyati: Explicit Metaphors in the Makkan Surahs and the Translation of Their Meanings into the Indonesian Language - Hamami AC, Muh. Nidom (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2022)
إن الأصل في المثل قائم على تشبيه شئ بشئ تشابه أو تماثل بينهما أو لوجود أكثر من عنصور تشابه. والأمثال إما أن يكون بسيطا أو ما يسمى باللأمثال المصرحة أي المشتمل على تمثيل مفرد بالمفرد و إما أن يكون مركبا أو ما يسمى بالأمثال الكامنة أي هي التي تقدم على شكل لوحة تصور أكثر من مفرد، ووجه تشبيه فيه لا يكون مأخوذا من مفرد بعينه، بل يكون مأخوذا منه ومن غيره أو من الصورة العامة. وضرب الأمثال في القرآن يستفاد منه بعض الأمور وهي: التذكير، والوعظ، والحث، والزجر، والإعتبار، والتقرير، وترتيب المراد للعقل، وتصريره في صورة المحسوس بحيث نسبته للفعل كنسبة المحسوس إلى الحس. وتأتي الأمثال في القرآن مشتملة على بيان تفاوت الأجر وعلى تحقيق أمر وإبطال أمر. وتتكون في السور المكية من 91 مثلا مصرحا. وهذه الأمثال المصرحة تنتشر في 33 سورة، وسورة إبراهيم هي أعلى الدرجات في عدد تكرار الأمثال المصرحة من جميع السور المكية. و تأتي ترجمة الأمثال المصرحة في السور المكية عند هيئة الترجمة من وزارة الشئون الدينية بمعنى: (1) النظير أو المقارنة، و(2) المثال أو النمودج، و(3) تشبيه شيئ بشيئ. The foundation of a proverb lies in the comparison of one thing with another due to similarity or resemblance between them, or because they share more than one element of likeness. Proverbs may be simple, known as explicit metaphors (al-amtsāl al-muṣarraḥah), which involve the comparison of one individual thing with another; or complex, known as implicit metaphors (al-amtsāl al-kāminah), which are presented in the form of an image depicting more than one element, where the aspect of comparison is not taken from one particular thing but from several, or from the general image as a whole. The use of parables in the Qur’an serves several purposes: reminding, admonishing, encouraging, warning, drawing lessons, confirming truths, making concepts clearer to the intellect, and presenting abstract meanings in tangible form, so that the relation of meaning to action becomes as clear as that of the tangible to the sense. In the Qur’an, parables also express differences in reward, confirm certain truths, and refute falsehoods.In the Makkan surahs, there are 91 explicit metaphors, spread across 33 surahs, with Surah Ibrāhīm ranking highest in the number of occurrences of explicit metaphors among all the Makkan surahs. In the translation issued by the Ministry of Religious Affairs, these explicit metaphors in the Makkan surahs are generally rendered with the meanings of (1) Analogy or comparison, (2) Example or model, and (3) The act of likening one thing to another.